Peer Comparison for Improving Senior High School Students’ Achievement Motivation - Azzahra, Salsabilla Arshalina; Yuniardi, Muhamad Salis; Putri, Aransha Karnilla Nadia (Tazkiya Journal of Psychology, 2025)
The desire for achievement creates motivation within the individual, where achievement motivation comes because of the need for achievement, which includes the desire to achieve success, complete difficult tasks, face challenges, and the desire to exceed others. This research aims to investigate whether peer comparison will affect achievement motivation as a manifestation of their need for achievement. This study used a quantitative method with a quasi-experimental design with two groups pre-test and post-test. A purposive sampling technique was utilized in this study, with the criteria of female and male senior high school students aged between 15-18 years old who have low scores in achievement motivation.  Participants in the experimental group will receive daily reports containing learning evaluations including the full scores and list of top ten students with the highest scores for six days. Achievement motivation was measured using the achievement motivation scale by Prihandrijani. Based on the results of the Wilcoxon test which was carried out after being given treatment, it was found that there was a significant difference in the subject's pre-test and post-test scores on the experimental group's achievement motivation with a value of p < .05. While in the control group, there was no significant difference seen from the value of p > .05. On the results of the Mann-Whitney test to see differences in achievement motivation in the experimental group and the control group, the value of p < .05 was obtained so that it can be concluded that giving treatment in the form of peer comparisons can influence individual achievement needs. This study result provides a new contribution to research related to achievement motivation and peer comparison which has been carried out using cross-sectional or observational methods.